2012
DOI: 10.1021/es300964d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Acid on Pyrene Removal from Water by Polycation-Clay Mineral Composites and Activated Carbon

Abstract: Pyrene removal by polycation-montmorillonite (MMT) composites and granulated activated carbon (GAC) in the presence of humic acid (HA) was examined. Pyrene, HA, and sorbent interactions were characterized by FTIR, fluorescence and zeta measurements, adsorption, and column filtration experiments. Pyrene binding coefficients to the macromolecules were in the order of PVPcoS (poly-4-vinylpiridine-co-styrene) > HA > PDADMAC (poly diallyl-dimethyl-ammonium-chloride), correlating to pyrene-macromolecules compatibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Experiments were conducted as published previously. 27 DCF (1 mg/L in tap water at pH-7.4) filtration by columns of QPVPcS and PVPcS composites (0.15 ± 0.01 g/g) and GAC was studied (4 replicates). The flow rate was 2 mL/min, 600 mL solution were filtered per column equivalent to 30 pore volumes (PV).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted as published previously. 27 DCF (1 mg/L in tap water at pH-7.4) filtration by columns of QPVPcS and PVPcS composites (0.15 ± 0.01 g/g) and GAC was studied (4 replicates). The flow rate was 2 mL/min, 600 mL solution were filtered per column equivalent to 30 pore volumes (PV).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Pyrene adsorption to a poly-4-vinylpyridine-co-styrene (PVPcS)-clay composite was high and increased in the presence of humic acid (HA) which was explained by the high affinity of HA to the composite and a cosorption mechanism. 27 In contrast, pyrene removal by GAC decreased in the presence of HA. Zedaka et al 28 demonstrated the efficient removal of atrazine by protonated PVPcS (HPVPcS)-clay composites.…”
Section: ■ Introductionmentioning
confidence: 96%
“…By gradually increasing the HA concentration to 80 mg OC/L, the retention of phenanthrene was hindered from 0.460 to 0.416 mg/g. At a low HA dose, the initial phenanthrene sorption increase was presumably due to the binding of phenanthrene to HA along with the sorption of HA onto modified palygorskite, forming a complexation of sorbed HA with phenanthrene [38]. The hydrophobic interaction mechanism was reported as the major factor responsible for the binding of PAHs to HA [39].…”
Section: Sorption Studiesmentioning
confidence: 99%
“…In addition, the pyridine group of the polymer can be further functionalized to improve composite performance [13,14]. Indeed, adsorbed functionalized PVP–MMT composites were efficient sorbents for filtration of a variety of pollutants including dissolved organic matter [14], pyrene [15], phenolic derivatives [16], pharmaceuticals [13] and pesticides [12,17]. …”
Section: Introductionmentioning
confidence: 99%